Documentação de fé: reflexões sobre os ex-votos e a sala das promessas do Santuário Nacional de Aparecida - Marañon, Eduardo Murguia; Souza, Bianca Gonçalves de [UNESP] (My University, 2012)
This article brings to light a reflection about the possibility to enlarge the notion about document. Beyond the French school explanation, and taking up again important author of Information Science campus, the debates exposes within the Brazilian Catholic dimensions is possible to extrapolate the revision about the document’s idea, which is generally restrict to informational spaces. The National Sanctuary of Aparecida protects in a specific room the votive offerings – objects leaved there whether to pay a promise or to thank for any miracle that someone believes receive it. It is mediation’ space and it is can be thought as an environment, because there are possibilities to establish mediations inside it. Although, the room of the promises is a sacred and profane place, it involves a Cathequesis mission, expositive, informational, in spite of this last characteristic does not be explicit. First of all, the article reflects about the room of the promises and follows analyzing the document’s comprehension; in a second moment we finish purposing to understand the votive offering as a faith’s document, because they assume the position as proof of miracles and received graces, and these special objects brings with them a materiality positive and a documental value which the room fo the promises give to them.

O presente artigo propõe a refletir sobre a possibilidade de expandir a reflexão acerca do documento. Para além de uma interpretação da escola francesa, retomando outros autores importantes do campo da Ciência da Informação, o debate visa a expor que dentro do campo religioso católico brasileiro, é possível extrapolar a revisão da ideia do documento apenas restrito a espaços ditos informacionais. O Santuário Nacional de Aparecida abriga uma sala na qual permanecem os ex-votos – objetos lá deixados para pagar ou agradecer por algum milagre recebido pelo devoto. É um espaço de mediação e ele mesmo pode ser pensado como um meio, pelas possibilidades de estabelecer mediações. No entanto, é um lugar sagrado, profano, catequético, expositivo, informacional, porém sem ter essa última característica explícita. O artigo inicia refletindo sobre a sala e caminhando na compreensão do documento, para então finalizar com uma propositura de compreender o objeto votivo como documento de fé, fazendo prova de milagres e graças alcançadas e, além disso, pela positividade que traz consigo materialmente falando e pelo valor documental que o espaço da sala lhe confere.
Documenting faith: considerations about the room of the promises at the National Sanctuary of Nossa Senhora Aparecida